Adhesives for wood and lignocellulosic materials - Kumar, Ramamurtinanda; Pizzi, A. 1946- (John Wiley & Sons, Inc. ; Scrivener Publishing LLC, 2019)
"The book is a comprehensive treatment of the subject covering a wide range of subjects uniquely available in a single source for the first time. A material science approach has been adopted in dealing with wood adhesion and adhesives. The approach of the authors was to bring out hierarchical cellular and porous characteristics of wood with polymeric cell wall structure, along with the associated non-cell wall extractives, which greatly influence the interaction of wood substrate with polymeric adhesives in a very unique manner not existent in the case of other adherends. Environmental aspects, in particular formaldehyde emission from adhesive bonded wood products, has been included. A significant feature of the book is the inclusion of polymeric matrix materials for wood polymer composites"-- Provided by publisher.
Keywords: Wood -- Bonding.; Adhesives.; Engineered wood.; elektronické knihy; electronic books